Risiko Ekonomi pada Praktek Risywah dan Ihtikâr - Siti Kadariah; Tuti Anggraini; Marliyah (Jurnal EMT KITA, 2022)
Ihtikâr in terminology is holding (hoarding) basic human goods to be able to gain profits by increasing the price and waiting for prices to soar in the market. According to the principles of Islamic law, whatever goods are permitted by Allah SWT to have them, then it is also lawful to be used as objects trading. Likewise, all forms that are forbidden to possess it are also forbidden to trade them. According to Yusuf al-Qardhawi, risywah is "money given to the ruler or employee, so that the ruler or employee imposes a punishment that benefits him. The type of research I use is a qualitative research type. Ihtikâr and Its Impact on the World Economy. There are several economic activities that benefit only one party but are prohibited by religion, such as gambling, usury, fraud (al-ghabn), tadlîs in buying and selling and hoarding (ihtikâr). For this reason, every economic activity must be based on a sense of transcendence. In general, risywah crimes have an impact on 3 important sectors in daily life, namely the individual, the community and the government.